Photonic Crystal Kinase Biosensor - MacConaghy, Kelsey I. (J Am Chem Soc, 2014)
[Image: see text] We have developed a novel biosensor for kinases that is based on a kinase-responsive polymer hydrogel, which enables label-free screening of kinase activity via changes in optical properties. The hydrogel is specifically designed to swell reversibly upon phosphorylation of a target peptide, triggering a change in optical diffraction from a crystalline colloidal array of particles impregnated into the hydrogel. Diffraction measurements, and charge staining, confirmed the responsive nature of the hydrogel. Moreover, the change in diffraction of the hydrogel upon treatment with kinase exhibited a time- and dose-dependent response. A theoretical model for ionic polymer networks describes the observed optical response well and can be used to quantify the extent of phosphorylation.